Determination of Optimal Indicators Based on Statistical Analysis for the State of Health Estimation of a Lithium-Ion Battery - Shi, Gaoya; Chen, Siqi; Yuan, Hao; You, Heze; Wang, Xueyuan; Dai, Haifeng; Wei, Xuezhe (Frontiers in Energy Research, 2021)
Online state of health (SOH) estimation is essential for lithium-ion batteries in a battery management system. As the conventional SOH indicator, the capacity is challenging to be estimated online. Apart from the capacity, various indicators related to the internal resistance are proposed as indicators for the SOH estimation. However, research gaps still exist in terms of optimal resistance-related indicators, online acquisition of indicators, temperature disturbance elimination and state of charge (SOC) disturbance elimination. In this study, the equivalent circuit model parameters are identified based on Recursive Least Square Method in dynamic working conditions in the lifespan. Statistical analysis methods including Multiple Stepwise Regression Analysis and Path Analysis are introduced to characterize the sensitivity of the parameters to SOH. Based on the above approach, the coupling relationship between the parameters is comprehensively analyzed. Results indicate that the ohmic resistance R0 and the diffusion capacitance Cd are the most suitable parameters for the SOH indication. Furthermore, R0 and Cd are proved to be exponentially correlated to the ambient temperature, while SOC demonstrates a quadratic trend on them. To eliminate the disturbance caused by the ambient temperature and SOC, a compensating method is further proposed. Finally, a mapping relationship between SOH and the indicators under normal operations is established. SOH can be estimated with the maximum error of 2.301%, which proves the reliability and feasibility of the proposed indicators and estimation method.